Biomimetic nanocomposite hydrogel networks for robust wet adhesion to tissues. (1st October 2021) - Chen, Yajun; Qin, Hanglan; Mensaha, Alfred; Wang, Qingqing; Huang, Fenglin; Wei, Qufu
Abstract: Designing multifunctional medical adhesives with strong adhesiveness under water is of great significance to achieve desirable therapeutic effects for promoting wound healing. However, its design is still challenging since most of existing hydrogel adhesive cannot work in wet environments. Here we proposed a tissue adhesive made from a combination of hydrogel matrix and nanocrystal fillers. The adhesion mechanism of this hydrogel adhesive relies on the absorption of interfacial water from tissue surfaces by hydrophilic hydrogel matrix, while the nanocrystals from the hydration process of calcium sulphoaluminate (CSA) contributes to strong cohesion. Subsequent noncovalent and covalent bonds between amine groups on tissue surfaces and catechol groups on polydopamine-intercalated silicate nanoflakes (PDA-Silicate) further improves the adhesion ability. The hydrogel adhesive with optimal compositions exhibited robust adhesiveness to different surfaces, with over 30 kPa of adhesive strength to porcine skin under water. Furthermore, chopped curcumin-loaded electrospun nanofibers were added into the precursor with optimized formulation to form nanofibers/hydrogel composite (NF-HG) in situ . The obtained NF-HG exhibited enhanced antibacterial activity, sustained drug release and good cytocompatibility. Taken together, this strategy may open new route to design versatile functional underwater adhesives.